ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ULANG JASA ENGLISH COURSE ( Studi Kasus Pada Konsumen ILP English Course Semarang ) - Adhikara, Nandiwardana Bawika; Sugiono, Sugiono (Faculty of Economics and Business Diponegoro University, 2015)
English is an international language which is now more and more in need. With thegrowing need for English, we should be able to master the English language. There are various ways to master the international language, one of them is to follow the course of the English language.One of the English educational institutions in Indonesia is an International LanguagePrograms or often called or known as ILP. With the growing needs of its customers to the English language course English language education institutions will be many more. However ILP total gross revenue in 2010 and 2011 decreased, increased in 2012 and decreased again in 2013. The decline in total gross revenue is expected because there are factors that influence its consumers do not make purchasing decisions on the institution of the English language. Therefore the aim of this study was to analyze factors that influence consumers in making purchasing decisions on English language education institutions services.The population in question in this research is that consumers ILP English CourseSemarang. The sample in this study Is most consumers ILP English Course Semarang, amounting to 120 people. Data type is primary. Methods of data collection using questionnaires. The analysis technique used is multiple regression with previously tested the validity test, reliability test and the classical assumption. The results of the analysis using regression shows that: Pricing, Quality Service, brand image, facilities, brand trust and satisfaction positive and significant impact on purchasing decisions on ILP English Course in Semarang, but the location factors and the promotion is not a significant influence on the purchase decision There-institution of the English language